Conceptual blocks of professional training for highly qualified personnel in higher physical culture and sports education - Masyagina, N.V.; Guba, V.P.; Leonteva, M.S.; Rodin, A.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to analyse and substantiate the conceptual blocks of scientific activity in the training of highly qualified personnel in higher physical education and sports education. Methods and structure of the study. Many years of theoretical and scientific research into the organisation of scientific activity in higher education institutions of the Russian Federation specialising in physical education and sport, focusing on the training of highly qualified scientific and teaching staff. Results and conclusions. The theoretical and practical rationale for scientific activity in physical education and sports universities indicates the need to develop criteria for improving human resources, laboratory facilities, improving educational programmes for training scientific and teaching staff, and increasing the publication activity of specialists in the identified main areas, are an indicator of the demand for scientific research results in the practical work of experts in the industry under consideration.